A morphometric study of glenoid cavity and its implication in shoulder arthroplasty and prosthetic designs - Shalom Elsy Philip; K R Dakshayani (Wolters Kluwer Medknow Publications, 2018)
Background and aims: Glenoid cavity of scapula is known for its variable morphology. The variations in the shape of glenoid cavity are due to the presence of a notch in its antero-superior part. The glenoid cavity is small and allows only a limited area for fixation devices. Knowledge of its morphology and dimensions would help in designing shoulder prosthesis for shoulder arthroplasty. Aim of current study is to determine the metrical and morphological variations [variation of shapes] of the glenoid cavity of the scapula for a better understanding and management of shoulder pathology. Materials and Method: One hundred dry scapulae of unknown sex availed from the Department of Anatomy, Mysore Medical College were studied. Varying shape of glenoid cavity based on presence of notch was also noted and measurements were taken with the digital Vernier caliper. Results: The glenoid cavity was found to occur in pear, oval, inverted comma shapes in frequency of 65.3%, 28.8%, 5.7% on right side and 62.2%, 27%, 10% on left side respectively. The mean anteroposterior diameter 1 and 2 were 24.05 ± 2.79 mm and 18.31 ± 2.36mm respectively. The mean Glenoid cavity index was 68.05 ± 4.87mm. Conclusion: The findings of the present study concurs with other studies, although there is slight difference in frequency of occurrence of shape of glenoid cavity which could be explained on the basis of ethnic and racial basis. The sound knowledge of various parameters of the glenoid cavity is important while performing shoulder arthroplasty and designing glenoid prostheses